Vitamin D receptor regulates intestinal inflammatory response in mice infected with blood stage malaria. (April 2018) - Mubaraki, Murad A.; Dkhil, Mohamed A.; Hafiz, Taghreed A.; Khalil, Mona F.; Al-Shaebi, Esam M.; Delic, Denis; Elshaikh, Kamal; Al-Quraishy, Saleh
Abstract: Malaria is a harmful disease affecting both tropical and subtropical countries and causing sometimes fatal complications. The effects of malaria-related complications on the intestine have been relatively neglected, and the reasons for the intestinal damage caused by malaria infection are not yet clear. The present study aims to evaluate the influence of intestinal vitamin D receptor on host-pathogen interactions during malaria induced in mice by Plasmodium chabaudi . To induce the infection, animals were infected with 10 6 P. chabaudi- parasitized erythrocytes. Mice were sacrificed on day 8 post-infection. The infected mice experienced a significant body weight loss and parasitaemia affecting about 46% of RBCs. Infection caused marked pathological changes in the intestinal tissue indicated by shortening of the intestine and villi. Moreover, the phagocytic activity of macrophages increased significantly (P < 0.01) in the infected villi compared to the non-infected ones. Infection by the parasite also induced marked upregulation of nuclear factor-kappa B, inducible nitric oxide synthase, Vitamin D Receptor, interleukin-1β, tumour necrosis factor alpha and interferon gamma-mRNA. It can be implied from this that vitamin D receptor has a role in regulating malarial infection. Highlights: Plasmodium chabaudi infection induced shortening of the intestine and its villi. Phagocytotic activity of macrophages declined significantly in the infected intestinal villi. The parasite infection induced upregulation of intestinal proinflammatory cytokines. Intestinal vitamin D receptor is upregulated during P. chabaudi infection.